Scaffold-based lung tumor culture on porous PLGA microparticle substrates - Kuriakose, Aneetta E. (PLoS One, 2019)
Scaffold-based cancer cell culture techniques have been gaining prominence especially in the last two decades. These techniques can potentially overcome some of the limitations of current three-dimensional cell culture methods, such as uneven cell distribution, inadequate nutrient diffusion, and uncontrollable size of cell aggregates. Porous scaffolds can provide a convenient support for cell attachment, proliferation and migration, and also allows diffusion of oxygen, nutrients and waste. In this paper, a comparative study was done on porous poly (lactic-co-glycolic acid) (PLGA) microparticles prepared using three porogens—gelatin, sodium bicarbonate (SBC) or novel poly N-isopropylacrylamide [PNIPAAm] particles, as substrates for lung cancer cell culture. These fibronectin-coated, stable particles (19–42 μm) supported A549 cell attachment at an optimal cell seeding density of 250,000 cells/ mg of particles. PLGA-SBC porous particles had comparatively larger, more interconnected pores, and favored greater cell proliferation up to 9 days than their counterparts. This indicates that pore diameters and interconnectivity have direct implications on scaffold-based cell culture compared to substrates with minimally interconnected pores (PLGA-gelatin) or pores of uniform sizes (PLGA-PMPs). Therefore, PLGA-SBC-based tumor models were chosen for preliminary drug screening studies. The greater drug resistance observed in the lung cancer cells grown on porous particles compared to conventional cell monolayers agrees with previous literature, and indicates that the PLGA-SBC porous microparticle substrates are promising for in vitro tumor or tissue development.